Mechanisms of Action of the New Antibodies in Use in Multiple Myeloma - Romano, Alessandra; Storti, Paola; Marchica, Valentina; Scandura, Grazia; Notarfranchi, Laura; Craviotto, Luisa; Di Raimondo, Francesco; Giuliani, Nicola (Frontiers in Oncology, 2021)
Monoclonal antibodies (mAbs) directed against antigen-specific of multiple myeloma (MM) cells have Fc-dependent immune effector mechanisms, such as complement-dependent cytotoxicity (CDC), antibody-dependent cellular cytotoxicity (ADCC), and antibody-dependent cellular phagocytosis (ADCP), but the choice of the antigen is crucial for the development of effective immuno-therapy in MM. Recently new immunotherapeutic options in MM patients have been developed against different myeloma-related antigens as drug conjugate-antibody, bispecific T-cell engagers (BiTEs) and chimeric antigen receptor (CAR)-T cells. In this review, we will highlight the mechanism of action of immuno-therapy currently available in clinical practice to target CD38, SLAMF7, and BCMA, focusing on the biological role of the targets and on mechanisms of actions of the different immunotherapeutic approaches underlying their advantages and disadvantages with critical review of the literature data.